Ukierunkowana zabawa - terapia dla dzieci z dysfunkcją integracji sensorycznej = Targeted fun - therapy for children with sensory integration dysfunction - Agnieszka Radzimińska; Katarzyna Strojek; Magdalena Weber-Rajek; Marcin Siedlaczek; Zuzanna Piekorz; Aleksander Goch; Anna Srokowska; Żukow Walery (Kazimierz Wielki University, 2015)
Radzimińska Agnieszka, Strojek Katarzyna,Weber-Rajek Magdalena, Siedlaczek Marcin, Piekorz Zuzanna, Goch Aleksander, Srokowska Anna, Zukow Walery. Ukierunkowana zabawa - terapia dla dzieci z dysfunkcją integracji sensorycznej = Targeted fun - therapy for children with sensory integration dysfunction. Journal of Education, Health and Sport. 2015;5(3):345-351. ISSN 2391-8306. DOI: http://dx.doi.org/10.5281/zenodo.37372 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A345-351 https://pbn.nauka.gov.pl/works/685683 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.02.2015. Revised 18.03.2015. Accepted: 21.03.2015.   Ukierunkowana zabawa - terapia dla dzieci z dysfunkcją integracji sensorycznej Targeted fun - therapy for children with sensory integration dysfunction   Agnieszka Radzimińska1, Katarzyna Strojek1,Magdalena Weber-Rajek1, Marcin Siedlaczek1, Zuzanna Piekorz1, Aleksander Goch1, Anna Srokowska2, Walery Zukow3   • 1.      Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska • Uniwersytet Mikołaja Kopernika w Toruniu, Collegium Medicum w Bydgoszczy, Katedra i Zakład Podstaw Kultury Fizycznej, Bydgoszcz, Polska • Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska   Adres do korespondencji: dr n. med. Agnieszka Radzimińska Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii ul. Marii Skłodowskiej-Curie 9, 85-094 Bydgoszcz e-mail: agnieszka.radziminska@gmail.com   Streszczenie Integracja sensoryczna (SI - Sensory Integration) jest to proces neurologiczny, podczas którego wrażenia sensorycznego ulegają przeorganizowaniu, proces dzięki któremu człowiek może prawidłowo funkcjonować w codziennym życiu (nauka, zabawa, wypoczynek). Terapia dzieci z zaburzeniem integracji sensorycznej polega na dostarczeniu dziecku odpowiednich bodźców (w zależności od typu zaburzenia - wzmacnianiu lub osłabianiu bodźców oraz przyzwyczajania do bodźców, na które dziecko jest nadwrażliwe/niedowrażliwe). Podczas terapii można wykorzystywać elementy terapii zajęciowej, dobierając materiały o odpowiedniej fakturze i tworzywa o różnej plastyczności (malowanie dłońmi, lepienie, modelowanie). Zadaniem terapeuty SI jest zapewnienie dziecku takiego ćwiczenia - zadania, którym samo może kierować i czerpać z  niego radość, tworząc  jednocześnie zadanie trudniejsze, angażujące złożone reakcje adaptacyjne układu nerwowego. Głównym celem prowadzenia ukierunkowanej zabawy u dzieci z zaburzeniami SI jest poprawa ich funkcjonowania w życiu codziennym, w relacjach z rodziną oraz rówieśnikami, poprzez obniżenie nadreaktywności dziecka lub jego dobodźcowanie.   Summary Sensory integration is the neurological process, during which sensory impressions are reordering process by which a person can properly function in everyday life (learning, fun, leisure). Treatment of children with sensory integration is the delivery of a child the right incentives (depending on the type of disorder - strengthening or weakening stimuli and habituation to stimuli. During the therapy can be used elements of occupational therapy, selecting materials with appropriate texture and materials of varying strength (painting with his hands, modeling, modeling). The task of the therapist SI is to ensure the child such an exercise - tasks, which itself can lead and reap the joy, while creating a more difficult task, involving a complex adaptive responses of the nervous system. The main aim of establishment-oriented fun for children with disorders of the SI is to improve their functioning in everyday life, in relationships with family and peers, by reducing overactivity of the child or his agitation.   Słowa kluczowe: ukierunkowana zabawa; terapia; dzieci z dysfunkcją integracji sensorycznej.   Keywords: targeted fun; therapy; children with sensory integration dysfunction.